New challenges for literature study in primary school English: building teacher knowledge and know-how through systemic functional theory - Macken-Horarik, Mary; Unsworth, Len (Onomázein, 2014)
Australian primary school teachers face two major challenges in their implementation of the national curriculum for English: literary study and multimodality. Whilst teachers and students frequently engage with texts like literary picture books, the requirement that teachers build children’s understandings of texts as patterned, aesthetic constructs is new. And it is especially demanding for teachers without specialized training in either literature or multimodality. They must learn to manage the expanded ‘reservoir’ of meaning in school English and develop ‘repertoires’ of semiotic understanding in the course of fulltime teaching (Bernstein, 2000). This paper emerges from a larger study that aimed to meet the challenge of literary study in English by introducing practicing teachers to a semiotic toolkit inspired by systemic functional grammatics. Grammatics, as Halliday (2002) interprets it, distinguishes the theory from the practice of grammar, the metalanguage from language in use. In our project, systemic functional grammatics included study not just of clause-level choices in language but their role in larger discourse frames and, via analogy, in images and multimodal texts. We made use of the ‘resemblance’ between focalization in print narratives and in bi-modal narratives picture books. Adapting semiotic principles like stratification and metafunction to national curriculum notions of ‘levels of analysis’ and ‘threads of meaning’, we used systemic functional (SF) theory to open up the potential of literature study for English teachers in NSW and Victoria, attempting to build understanding about the ‘uses’ of grammatics for a relatively uninformed group of ‘users’ (Martin et al., 2013). Because of the need to manage the theory-practice nexus in professional learning, we attempted to characterize ‘knowledge about’ images in narrative in accessible and systematic ways and to relate this to pedagogic ‘know-how’ in primary teaching and assessment of narrative. The paper introduces the analytical framework we developed to represent and develop knowledge and know-how in primary school literature study. It shows how we used the framework to benchmark teacher starting-points as they commented on students’ responses to a picture book called The Great Bear by Armin Greder and Libby Gleeson (1999). It overviews input provided to teachers in workshops based on SF principles such as system, stratification and metafunctions. Finally, it overviews our initial findings based on our analysis of follow-up interviews with two teachers as they reflected on students’ responses to The Tunnel, by Anthony Browne (1989). Changes are arrayed on clines produced to account for shifts in teacher knowledge and know-how. Early results of our project are very encouraging, providing evidence of significant if varied growth in teachers’ orientations to narrative meaning and increased levels of meta-semiotic awareness. The paper concludes with reflections on the use of SF grammatics for meeting the challenges of literature study in primary school English in an era of multimodality.